Localized Interleukin-12 for Cancer Immunotherapy - Nguyen, Khue G.; Vrabel, Maura R.; Mantooth, Siena M.; Hopkins, Jared J.; Wagner, Ethan S.; Gabaldon, Taylor A.; Zaharoff, David A. (Frontiers in Immunology, 2020)
Interleukin-12 (IL-12) is a potent, pro-inflammatory type 1 cytokine that has long been studied as a potential immunotherapy for cancer. Unfortunately, IL-12’s remarkable antitumor efficacy in preclinical models has yet to be replicated in humans. Early clinical trials in the mid-1990’s showed that systemic delivery of IL-12 incurs unintentional signaling and dose-limiting side effects. Yet, it is IL-12’s pleiotropic activity, i.e. its ability to engage multiple effector mechanisms and reverse tumor-induced immunosuppression, that makes it such an intriguing therapeutic. The development of strategies which maximize IL-12 delivery to the tumor microenvironment while minimizing systemic exposure are of increasing interest. Diverse IL-12 delivery systems, from immunocytokine fusions to polymeric nanoparticles, have demonstrated robust antitumor immunity with reduced adverse events in preclinical studies. Several localized IL-12 delivery approaches have recently reached the clinical stage with several more at the precipice of translation. Taken together, localized delivery systems are supporting an IL-12 renaissance which may finally allow this potent cytokine to fulfill its considerable clinical potential. This review begins with a brief historical account of cytokine monotherapies and describes how IL-12 went from promising new cure to ostracized black sheep following multiple on-study deaths. The bulk of this review is a comprehensive account of developments in localized delivery strategies for IL-12-based cancer immunotherapies. Advantages and limitations of different delivery technologies are highlighted. Finally, perspectives on how IL-12-based immunotherapies may be utilized for widespread clinical application in the very near future are offered.